Bekvaem: integrative data exploration of genomic data - Hofmann, Andreas; Müggenburg, Jan; Heermann, Dieter W. (Universität, 2019)
Using modern open-source libraries for web-based visualizations and data-processing, Bekvaem, a generic framework for the creation of data explorat...